Environment, Health and Labor Market - Xavier Pautrel (Fondazione Eni Enrico Mattei (FEEM), 2017)
We re-examine the impact of environmental taxation on health and output, in the presence of labor market frictions. Our main findings are that matching process and wage bargaining introduce new channels of transmission of environmental taxation on the economy such that assuming perfect labor market leads to over-estimate the positive impact of environmental taxation on health. We also demonstrate that rising abatement expenditures as a way of tightening the environmental policy would be better for health than increasing environmental tax in the presence of market labor imperfections.
Keywords: I1; J2; J64; Q58; 330; Environmental Policy; Health; Labor Market; Search; Unemployment